2022
DOI: 10.1038/s43247-022-00574-8
|View full text |Cite
|
Sign up to set email alerts
|

Projected climate variability of internal waves in the Andaman Sea

Abstract: The Andaman Sea, in the northeast Indian Ocean, is renowned for large-amplitude internal waves. Here, we use a global climate model (CanESM5) to investigate the long-term variability of internal waves in the Andaman Sea under a range of shared socioeconomic pathway (SSP) scenarios. SSPs are future societal development pathways related to emissions and land use scenarios. We project that mean values of depth-averaged stratification will increase by approximately 6% (SSP1-2.6), 7% (SSP2-4.5), and 12% (SSP5-8.5) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…HYCOM's performance in SC PAC, where the shelf‐slope regions of the French Polynesian Islands are the main generation sites, lags behind HRET8.1 by 7.5%. Strong stratification and complex bathymetry along the Andaman Nicobar Ridge makes BoB a strong region for internal tides (e.g., Yadidya and Rao, 2022a, 2022b; Yadidya et al., 2022). HYCOM removed 3% more variance in BoB when N 2 is included.…”
Section: Resultsmentioning
confidence: 99%
“…HYCOM's performance in SC PAC, where the shelf‐slope regions of the French Polynesian Islands are the main generation sites, lags behind HRET8.1 by 7.5%. Strong stratification and complex bathymetry along the Andaman Nicobar Ridge makes BoB a strong region for internal tides (e.g., Yadidya and Rao, 2022a, 2022b; Yadidya et al., 2022). HYCOM removed 3% more variance in BoB when N 2 is included.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it becomes important to note that the interannual or even climatic scale evolution of internal tidal waves activity must be considered to better understand the future evolution of the global climate. Especially since thanks to the CanESM5 global climate model, Yadidya and Rao (2022) have just shown that in the Andaman Sea and Bay of Bengal, towards the end of this century, for both optimistic and pessimistic SSP scenarios, the increase in depthaveraged stratification will result in an increase in IT activity in these two regions. Knowing that the continental slope of northern Brazil is a place of high generation of IT, which therefore depends on stratification, it is hereby critical to understand how IT activity will evolve in the coming decades in order to better anticipate the climate, and thus better adapt public policies at national and international levels to the global context of climate change.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Climate change might increase stratification globally (Reid et al 2009, Capotondi et al 2012, Li et al 2018), which will likely increase the energy contained in (Yadidya and Rao 2022) and the mixing induced by internal tides (Haigh et al 2020). Based on our study, global warming might also cause internal tides to be generated shallower on continental slopes.…”
Section: Discussionmentioning
confidence: 61%
“…The depth-integrated and global total energy contained in the internal tide has been investigated before (e.g., Vic et al, 2019;st. Laurent and Garrett, 2002;Yadidya and Rao, 2022), but the actual depth of internal-tide generation has not yet been considered in the present context and on a global scale. Yet, the depth of internal-tide generation is likely of relevance to cold-water corals, since it is this depth where the highest internal-wave excursions and more intense mixing occur near the seafloor (Frederiksen et al 1992, chapter 3).…”
Section: Introductionmentioning
confidence: 99%